A STUDY OF THAI COUNTRY MUSIC PATTERN BETWEEN EARLY THAI COUNTRY MUSIC AND DIGITAL THAI COUNTRY MUSIC PERIOD - BHUMITHAVARA , KRITTAVIT (Journal of Suan Sunandha Arts and Culture, 2022)
The objective of this article is to show a comparison of Thai country music pattern at the present time changed from the past. Typically, Thai country music represents Thai ways of life, cultures, and reflect a condition of Thai society via simple language and environment. Most of them tell stories of people in rural areas, living far from urban areas. This academic article examined Changing styles of Thai country music from the past to the present too: Pattern of Musical instruments Lyrical content Performance on stage Tool and equipment for music production and Thai country music singing contests This study illustrates the development and changes of Thai country music pattern as the time is constantly moving forward to be the guideline for other Thai country music research in the future.